Orbital corticosteroid injections for the treatment of active thyroid eye disease - Eid, Kevin T.; Kally, Peter M.; Kahana, Alon (Frontiers in Ophthalmology, 2024)
Purpose: To study the efficacy of orbital injections of triamcinolone acetonide mixed 1:1 with dexamethasone in the treatment of active thyroid eye disease.Patients that received orbital injection(s) of triamcinolone acetonide mixed 1:1 with dexamethasone for thyroid eye disease were included in this retrospective study. Demographic and clinical data were collected from the pre-treatment and 1 month follow up evaluations.Clinical data included subjective pain and diplopia scores, best-corrected visual acuity, Intraocular pressure, extraocular motility, clinical activity score, Hertel exophthalmometry, and upper eyelid margin to reflex distance.Results: Fifteen patients, 33 orbital injections, were included in the study. The average patient age was 59.2 years (SD ± 13.0) and 89% female. Subjectively, 67% of patients reported improvement of orbital pain and pressure versus 28% stable and 5% worse (p <0.001). Postprocedure clinical activity score decreased from 3.84 to 3.00 (p = 0.0004). There were no significant differences in upper eyelid margin to reflex distance (4.1 ± 1.4 mm vs. 4.3 ± 2.6 mm, p = 0.45), Hertel exophthalmometry (21.7 ± 9.4 mm vs. 21.8 ± 7.6 mm, p = 0.56), or extraocular motility (21% improved vs. 72% stable and 7% worsening, p = 0.50). No steroid-responsive increases in intraocular pressure or injection-related complications were reported.Orbital steroid injections can successfully reduce symptoms of TED and may be a reliable tool in the treatment of TED as a relatively safe, fast-acting, efficacious treatment option, particularly as a bridge to other therapies.